Evaluation of The CIPP Model on The Tahfidz Program in Islamic Boarding Schools - Atikah Markhamah Ayyusufi; Ari Anshori; Muthoifin Muthoifin (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of this article is to describe the results of the comparative evaluation of the implementation of the tahfidz program between Pondok Darul Fithrah Tawangsari and PPTQ Ulul Albab Polokarto Sukoharjo in 2021/2022 in terms of the CIPP evaluation model for the students of the Ulya unit between the two Pesantren. This article used a qualitative type and includes field research. Data collection techniques used were observation methods, interview methods, questionnaires (questionnaires), and documentation methods. The findings of the research show that the implementation of the tahfidz al-Qur'an program at Pondok Darul Fithrah and PPTQ Ulul Albab has been going well. The context aspect between Pondok Darul Fithrah and PPTQ Ulul Albab tahfidz program is in the very good category. The input aspect of the tahfidz program at Pondok Darul Fithrah is in a good category, while the PPTQ Ulul Albab is in a very good category. In the process aspect, the tahfidz program at Pondok Darul Fithrah and PPTQ Ulul Albab are both in the very good category. Finally, the product aspect of the tahfidz program at Pondok Darul Fithrah is in a good category, there is one indicator in the form of a memorization target not being maximized with a percentage of 50-60%, while PPTQ Ulul Albab is in the very good category with a percentage of 90%.